The chemotherapeutic effects of synthetic and natural compounds - Motau, Tshegofatso Harold (My University, 2015)
Plasmodium falciparum remains the most virulent cause of malaria. With increasing drug resistance to artemisinin and other antimalarial drugs, combined with an absence of an effective vaccine, there’s a critical need for new agents to complement existing treatment and prophylaxis. Therefore, the aim of the study was to evaluate the in vitro antimalarial activity and potential toxicity to mammalian cells of select synthetic and natural colourants, nucleoside and imidazo[1,2a]pyridine (IP) analogues on the erythrocytic stages of the 3D7 chloroquine-sensitive strain of P. falciparum. The P. falciparum 3D7 strain was maintained in vitro according to standard methods. Quinine and chloroquine were used as positive controls. The tritiated hypoxanthine incorporation assay was used for evaluating the ability of test compounds to inhibit the growth of P. falciparum. Active test compounds were tested in combination studies with quinine. Uninfected human red blood cell (RBC) toxicity was analysed spectrophotometrically. The ability of test compounds to inhibit -haematin formation, a metabolic pathway that sequesters toxic haem within the parasites, was determined. Cytotoxic activity of active compounds was evaluated on two human cell lines (HEK293 and K562) using the [3H]-thymidine incorporation assay. Data was analysed using the one-way ANOVA test and reported as the mean ± standard deviation of at least triplicate experiments and significant difference when p < 0.05. Of the 56 compounds tested, the synthetic colourants showed the most potent antimalarial activity. Methylene blue and safranin O were most potent with IC50 values of 4.19 ± 0.16 nM and 86.50 ± 2.61 nM, respectively, compared to quinine (IC50: 103.90 ± 8.30 nM), and displayed negligible toxicity to uninfected human RBCs. Combination studies with methylene blue and quinine demonstrated a synergistic interaction. Methylene blue also demonstrated the highest selectivity indices (480 and 968) compared to quine (180). Curcumin (diferuloylmethane), a natural extract was active (IC50: 2.29 ± 0.18 μg/ml) against P. falciparum, but significantly (p < 0.05) less potent than quinine. Curcumin was 78-fold more active in inhibiting -haematin formation than quinine, indicating of a possible mechanism of action. The most active nucleoside analogue, JLP118.1 (IC50: 1.79 ± 0.12 μM), demonstrated inhibitory activity against the trophozoite stage of P. falciparum. The imidazopyridine analogue, IP-4, displayed the least potent antimalarial activity (IC50: 15.3 ± 0.41 μM) of the synthetic compounds tested, with low selectivity indices < 1. The study has confirmed the potent antimalarial activity and relative safety of methylene blue as well as its potential as an antimalarial drug. The nucleoside and imidazopyridine analogues showed promising activity and with structural modification their potency and selectivity indices may be enhanced.
A dissertation submitted to the Faculty of Health Sciences, University of the Witwatersrand, Johannesburg,in fulfillment of the requirements for the degree of Master of Science in Medicine. Johannesburg, South Africa, 2015
Keywords: Parasitic Diseases; Malaria; Plasmodium falciparum